A pre-tracer approach for improving the accuracy of metabolic measurements by hyperpolarized nuclear magnetic resonance - Li, Lin Z. (Quantitative Imaging in Medicine and Surgery, 2016)
Hyperpolarized nuclear magnetic resonance (HP-NMR) can probe the reaction kinetics of metabolic enzymes in vivo (1), and the translation of this technology into human patients based on the most commonly used tracer 13C-pyruvate has been initiated in recent years (2). Currently the metabolite signal ratios are used as indicators for biological processes in healthy and diseased status. For example, to probe the reaction of lactate dehydrogenase (LDH) with hyperpolarized 13C-pyruvate, the peak, mean, or integrated (area-under-curve) signal ratios of 13C-lactate to 13C-pyruvate are used to differentiate tumor and normal tissues, and to evaluate treatment response (3-5). However, these ratios do not have clearly defined biochemical meaning, and it is desirable to quantify the reaction rate constants.